Variations on RNA folding and alignment: lessons from Benasque - Bompfünewerer, Athanasius F.; Backofen, Rolf; Bernhart, Stephan H.; Hertel, Jana; Hofacker, Ivo L.; Stadler, Peter F.; Will, Sebastian (Journal of mathematical biology, 2008)
Dynamic programming algorithms solve many standard problems of RNA bioinformatics in polynomial time. In this contribution we discuss a series of variations on these standard methods that implement refined biophysical models, such as a restriction of RNA folding to canonical structures, and an extension of structural alignments to an explicit scoring of stacking propensities. Furthermore, we demonstrate that a local structural alignment can be employed for ncRNA gene finding. In this context we discuss scanning variants for folding and alignment algorithms.